Bilinguismo indígena: - Muniz, Simara de Sousa (2023)
This work presents a study on Indigenous Bilingualism, considering the languages in use, in the Apinayé and Krahô social domains, indigenous peoples who live in the north of the state of Tocantins, speakers of the homonymous language belonging to the Macro Jê trunk and the Jê Linguistic Family. The Apinayé population is 3,009 people spread over 53 villages, and the Krahô population is 3,848 people spread over 55 villages (DSEI, 2022). The objective was to identify and analyze the types and dimensions of bilingualism in the Apinayé, village São José, and Krahô, Manoel Alves Pequeno communities, based on ethnographic, sociolinguistic and ethnosociolinguistic studies. The research is qualitative and is based on studies by Günther (2006) and Vasconcelos (2009). It is a participatory, collaborative and critical ethnography based on the theories of Ezpeleta and Rockwell (1989), Erickson (1984) and Tomas (1993). Data were collected at the Laboratory of Indigenous Languages (LALI/UFNT) from studies carried out by Severina Alves de Almeida carried out in the Apinayé São José village: Ethnossociolinguistics and Literacy: Contributions to an Apinayé Indigenous Bilingual and Intercultural Curriculum (2015), and in the Krahô by researchers Marta Virginia de Araújo Batista Abreu (2012) who studied the Sociolinguistic Situation of the Krahô and Marcilene de Assis Alves Araújo (2015) who carried out a very important study on the Interaction Events in Krahô (Jê) Rituals, identifying their Contributions to Bilingual Education in Manoel Alves Pequeno Village. The theoretical front is broad and includes categories such as; Indigenous Education; Bilingual and Intercultural Indigenous Education; Bilingualism; Indigenous Bilingualism; Indigenous Peoples of Brazil and Tocantins; Ethnolinguistics; Sociolinguistics; Ethnography of Communication; Literacy, Language Contact; Indigenous Languages of Brazil; Linguistic and Ethnic Identity, among others. The theoretical foundation is anchored in the classic works of Malinowski (1978); Nimuendaju (1983); Da Matta (1975); Maher (2007); Rodrigues (1988, 2002, 2013), Erickson (1984; 1988), Ezpeleta & Rockwell (1989), Thomas (1993). In addition to these, we resort to more current publications, for example, André (2004), Bortoni-Ricardo, (2005); Sousa (2006), Macedo (2006), Beaud & Weber (2007), Vasconcelos (2009), Van Dijk (2001; 2012), Street (2007, 2014), Harmers and Blanc (2000), Rojo (2009), Albuquerque (2007), Almeida (2015), among other authors. The results were analyzed in the light of Ethnossociolinguistics and its epistemological framework, when we identified five dimensions of bilingualism: by relative competence; acquisition age; presence or not of L2-speaking individuals in the environment in question and the status of the two languages, called dominant, child, adolescent and adult, endogenous, subtractive, bicultural and intercultural bilingualism. In other words, the bilingualism of the Apinayé indigenous communities of the São José and Krahô villages of Manoel Alves Pequeno is Individual and Social and is characterized by its multidimensionality, it is also a consecutive child bilingualism. In this sense, the research contributes to the linguistic studies related to Bilingualism in indigenous societies, generating visibility for the more than 300 peoples who live in Brazil.